Study of the inhibitory effects of some medicinal plants extracts on growth of Listeria monocytogenes isolated from human, cow and sheep in Al-Qadisiyah governorate - Al-Nasrawi, Huda Abdal-Hadei Ali (The Iraqi Journal of Veterinary Medicine, 2018)
This study aimed to evaluate-the inhibitory effects of ethanolic and-chloroformic-extracts of local medicinal plants as Oak (Quercus-acuta), Thyme (Thymus vulgaris) and Cinnamon (Cinnamomum-zeylanicum) prepared in different concentrations (50, 100, 200 and 400 mg/ml) against the growth of Listeria-monocytogenes isolated from infected humans and animals and comparing their activity with effectiveness of the standard antibiotics. The results showed detection of Listeria-monocytogenes in 3 of (50) blood samples collected from aborted woman making 6% samples, while the detection rates of Listeria-monocytogenes in milk samples collected from sheep and cattle were 4% (4/100) and 9.16% (11/120) respectively. The ethanolic and-chloroformic extracts-of Thyme as well as, chloroformic extracts of Oak and Cinnamon at concentrations (50 and 100 mg/ml) showed significant antibacterial activity against the growth of Listeria-monocytogenes isolates from humans, while the ethanolic extracts of Oak and Cinnamon did not show any antibacterial activity against the growth of same bacterial isolates. The ethanolic and chloroformic extracts of Thyme, as well as chloroformic extracts of Cinnamon at concentrations (50 and 100 mg/ml) showed antibacterial activity against growth of Listeria monocytogenes isolates of cattle, while ethanolic and chloroformic extracts of Oak and ethanolic- extracts of Cinnamon did not show any activity against growth of the same isolates. The results showed that all extracts have antibacterial activity against growth of-Listeria monocytogenes isolates-of sheep, except ethanolic extracts of Cinnamon at all tested concentration; as well, the chloroformic extracts of Thyme at concentrations (5o and 100 mg/ml) didn’t show any inhibitory activity for the growing of the same Listeria. monocytogenes isolates. Most of the results showed high antibacterial activity against growth of all Listeria .monocytogenes isolates from human and animals compared with negative control and this depends on their inhibition zones. In this study, we used six standard antibiotics as a positive control for Listeria monocytogenes, where rifampin. (5mcg),-chloramphenicol.(10mcg), streptomycin (25 mcg) and amoxicillin/clavulanic acid-(20/10mcg) were effective in inhibition the growth of all L. monocytogenes isolates from human and animals, while cefotaxime. (10 mcg) and novobiocin. (30 mcg) showed no inhibitory effects against growth of all L. monocytogenes isolates.